Luminescent spherical particles of lanthanide-based infinite coordination polymers with tailorable sizes - Arroyos, Guilherme [UNESP]; Frem, Regina C. G. [UNESP] (Royal Society of Chemistry (RSC), 2020)
Infinite coordination polymers (ICPs) are compounds usually obtained as spherical particles exhibiting amorphous phases in powder X-ray diffraction patterns. In the present work, we report an ICP system based on rare-earth ions with pyrazole-3,5-dicarboxylate as a linker and malonate as a coordination modulator. The compounds exhibit a 2D MOF structure. Three different synthetic routes were used, namely microwave-assisted, solvothermal and gel diffusion. The syntheses yield single-phase spherical particles, which were characterized by PXRD, 1H NMR, CHN, FTIR, TGA, SEM and TEM. Photoluminescence spectroscopy was carried out to study the luminescence properties of the Eu3+ and Tb3+-based samples. With the different-sized particles obtained, we could elucidate the intricate microstructure of the spheres and propose a reason behind the observed amorphous phases in the PXRD patterns.